2018
DOI: 10.1177/0265407518806582
|View full text |Cite
|
Sign up to set email alerts
|

Temporal dynamics of couples’ communication behaviors in conflict discussions: A longitudinal analysis

Abstract: Negative and positive conflict communication predicts long-term relationship satisfaction. However, some studies show harmful effects and others show beneficial effects of negative conflict communication on long-term relationship satisfaction. One reason for the heterogeneous results might be that most studies focused on aggregated behaviors across a conflict interaction but neglected the temporal dynamics within such an interaction. This study examined whether individual initial levels and temporal trajectori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 37 publications
(102 reference statements)
0
10
0
Order By: Relevance
“…As a result, we are left with decontextualized behaviors displayed by, and inadvertently attributed to, just one partner, thus grossly oversimplying the emergent and dyadic character of couple interaction (S. Duncan, Kanki, Mokros, & Fiske, ). Sequential analysis has proven to be difficult to implement—in part because repeated instances of behavioral sequences are necessary for reliable estimates of those sequences—but this problem can be overcome, for example, by collecting continuous ratings of behavior (e.g., Ross et al, ), by studying how behaviors unfold during the entire span of conversations (e.g., Kuster et al, ; Leuchtmann et al, ), and by undertaking intensive analysis of specific behavioral sequences hypothesized to be critical for problem‐solving or relationship maintenance. For example, in a methodologically elegant study, Bloch, Haase, and Levenson () focused intensely on how spouses mutually downregulate negative emotions and experiences during a problem‐solving conversation, with results suggesting that ineffective attempts to contain negative emotions, more so than the mere presence of negative affect, are most likely to compromise wives' relationship satisfaction.…”
Section: Marital Interactionmentioning
confidence: 99%
“…As a result, we are left with decontextualized behaviors displayed by, and inadvertently attributed to, just one partner, thus grossly oversimplying the emergent and dyadic character of couple interaction (S. Duncan, Kanki, Mokros, & Fiske, ). Sequential analysis has proven to be difficult to implement—in part because repeated instances of behavioral sequences are necessary for reliable estimates of those sequences—but this problem can be overcome, for example, by collecting continuous ratings of behavior (e.g., Ross et al, ), by studying how behaviors unfold during the entire span of conversations (e.g., Kuster et al, ; Leuchtmann et al, ), and by undertaking intensive analysis of specific behavioral sequences hypothesized to be critical for problem‐solving or relationship maintenance. For example, in a methodologically elegant study, Bloch, Haase, and Levenson () focused intensely on how spouses mutually downregulate negative emotions and experiences during a problem‐solving conversation, with results suggesting that ineffective attempts to contain negative emotions, more so than the mere presence of negative affect, are most likely to compromise wives' relationship satisfaction.…”
Section: Marital Interactionmentioning
confidence: 99%
“…These steps were repeated for the coding of the second partner. This coding method demonstrated good validity in previous studies (Kuster et al, 2015;Zemp et al, 2016Zemp et al, , 2017, and rater teams achieved a high interrater reliability (i.e., Cohen's kappa ≥ 0.90) in previous research (Zemp et al, 2017;Leuchtmann et al, 2019). A master coder from the University of Zurich trained the first author.…”
Section: Affective Behaviormentioning
confidence: 83%
“…Some data of the larger research project has already been used in other publications (e.g., Kuster et al, 2015; Leuchtmann et al, 2019; Neysari et al, 2016). The present article is the first to investigate couples’ language use across interaction contexts, representing unique research questions, analytic strategies, and models.…”
Section: Methodsmentioning
confidence: 99%
“…With the help of a list about common areas of disagreement (PAQ A; Heavey et al, 1995) and a trained research assistant, partners collaboratively identified a source of tension in their relationship they wanted to discuss. Among the most frequently discussed conflict topics were communication with the partner, annoying habits of the partner, and finances (Kuster et al, 2015; Leuchtmann et al, 2019). After deciding on the topic, participants were left alone in the room and videotaped while discussing the issue.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation